Characteristics of fig (Ficus carica L. var. Ipoh Blue Giant) syconium during growth, maturation and on-tree ripening - Mat Jusoh, Nur Athirah (2022)
Lately, fig (Ficus carica) has become one of the new crops among Malaysian growers. It was suggested that it is a potential crop that can improve Malaysian horticultural and downstream product industries. Even so, the study on fig grown in country is very lacking. Most of the previous studies were mainly conducted in subtropical countries. Therefore, a study on common fig that grown under Malaysia climate was carried out to determine its characteristics during growth, maturation and on-tree ripening. This study was carried out on fig trees cultivated commercially at the Selangor Fruit Valley, Rawang, Selangor. The bud of fig was tagged and its development was monitored weekly. Data were recorded from 1st week after bud emergence (WAB) until syconium matured and fully ripened on tree. The physical, physiological, chemical and structural characteristics of fig syconium during growth, maturation and on-tree ripening was obtained. Results obtained showed that fig var. Ipoh Blue Giant (IBG) cultivated in Malaysia took 12 WAB to develop from a tiny bud into a mature syconium and followed by 6 days on-tree ripening and finally senescent. Based on fruit size (diameter, volume and weight), IBG fig exhibited a double sigmoid growth curve. From the physiological characteristics, IBG fig exhibited climacteric ripening by having a burst in ethylene and carbon dioxide emission during ripening at day 0 with 24.35 μL C2H4.kg-1.h-1 and 74.5 mL CO2.kg-1.h-1, respectively. The green colour of syconium gradually disappeared and turned red as it matured and ripened. The pulp firmness increased as weeks after bud emergence progressed, and decreased to 1.38 N as ripening took place. The soluble solids concentration increased as week after bud emergence progressed and peaked to 16.69% SSC at ripening day 5. The titratable acidity was initially increased as weeks after bud emergence progressed and peaked to 8.32% during 11 WAB but decreased as it ripened. While, the pH showed inversely trend with titratable acidity where pH decreased from 6.29 to 4.93 during weeks after bud emergence progressed, but increased gradually as fig ripened. Results of analysis also revealed that the sugar content increased as on-tree ripening days progressed with more than 65% increment. However, the total pectin content did not show any significant changes during growth and development. The observation of structural changes of fig syconium during growth, maturation and on-tree ripening were in accordance with the changes in syconium size. Fig syconium underwent cell division during 1 WAB, cell enlargement during 4 and 7 WAB and enlargement of intercellular spaces during day 3 of on-tree ripening. In brief, the optimum harvesting stage of IBG fig grown under Malaysia climate is at day 2 of on-tree ripening. As it has become a new potential crop in Malaysia, information on the optimum harvesting stage is crucial especially on postharvest handling process in order to reduce the loss faced by growers and sellers.